Hittite Toponymy - Kryszeń, Adam (Altorientalische Forschungen, 2019)
This article provides an up-to-date overview of the collection of toponyms in the Hittite corpus. It discusses the general features of the inventory of place names and their distribution according to various criteria, including dating, language and specific context. Particular attention is paid to the geographic typology of toponyms applied by the Hittite scribes (from both synchronic and diachronic perspectives). It is hoped such a general sketch could offer comparative material for broader, more inclusive studies on the geographical concepts in the Ancient Near East.